D → Pℓ + ℓ − decays assisted by QCD light-cone sum rules - Anshika Bansal; Alexander Khodjamirian; Thomas Mannel (Journal of High Energy Physics)
Abstract We suggest a new method to analyse the rare D (s) → Pℓ + ℓ − decays (P = π, K), combining QCD light-cone sum rules (LCSR) with hadronic dispersion relations. As our main study case, we consider the D + → π + ℓ + ℓ − mode which attracts much of interest from the point of view of GIM cancellation and potential new sources of the FCNC c → u transitions. The hadronic amplitude of this decay is dominated by the combination of weak annihilation with the emission of a virtual photon. This D + → π + γ ∗ amplitude is calculated at spacelike photon virtualities, −q 2 ≫ Λ QCD 2 $$ Λ_{QCD}^2 $$ , using LCSR with pion distribution amplitudes. The LCSR results are then fitted to the hadronic dispersion relation in the variable q 2. The fit allows us to determine relative phases of the ρ-, ω- and ϕ-meson terms and to estimate the contributions of heavier hadronic states. The latter are parameterized in two different ways: first, with a z-expansion and second, using a model with excited vector-meson resonances. The resulting D + → π + ℓ + ℓ − width obtained from the LCSR-assisted dispersion relation is not much smaller than the current upper bound measured by LHCb collaboration. In comparison with our result for the dominant D + → π + γ ∗ transition, the contribution induced by the short distance c → uℓ + ℓ − quark transition generated by the effective O 9 operator in Standard Model turns out to be practically invisible. To detect its effect, one readily needs an enhancement of the coefficient C 9 from non-standard effects by many orders of magnitude. We also establish new U-spin symmetry relations between the amplitudes of D → Pℓ + ℓ − decays and apply our method to the Cabibbo-favoured modes D s + → π + ℓ + ℓ − $$ D_s^{+}→ π^{+}{\ell}^{+}{\ell}^{-} $$ and D 0 → K ¯ 0 ℓ + ℓ − $$ D^0→ {\overline{K}}^0{\ell}^{+}{\ell}^{-} $$ which proceed via the same weak annihilation mechanism.